Social Panorama of Latin America 2005 - United Nations (United Nations, 2006)
The 2005 edition of the Social Panorama of Latin America analyses recent poverty trends and the increase in migrant remittances, together with their impact on the well-being of the region's population. The analysis seeks to explore the question as to whether the demographic transition taking place in the Latin American countries over the past 15 years has helped to narrow the long-standing gaps between different socio-economic groups' and areas' mortality and birth rates. Attention is also drawn to the magnitude of the HIV/AIDS epidemic in Caribbean countries and to the reversal of its skewed gender distribution, which has had a devastating impact on households and the community at large. Finally, this edition looks at major changes in the health sector.